1999
DOI: 10.1165/ajrcmb.20.1.3251
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Gene Expression in Human Fetal Lung In Vitro

Abstract: Neonatal respiratory function depends on the development of a well-formed pulmonary capillary bed. Vascular endothelial growth factor (VEGF) is a potent inducer of endothelial cell growth and angiogenesis. High levels of VEGF protein and messenger RNA (mRNA) have been detected in the developing lung, suggesting that VEGF plays a role in the development of the pulmonary capillary bed. To begin to understand the role of VEGF in human lung development, we explored the regulation of VEGF gene expression and the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0
15

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 39 publications
6
99
0
15
Order By: Relevance
“…In that paper, Rp-cAMP, a cAMP antagonist, suppressed VEGF expression induced by PGE2 (23). cAMPdependent increase in VEGF expression was also observed in isolated organs such as perfused rat lungs and human fetal lung explants (24,25).…”
Section: Discussionmentioning
confidence: 82%
“…In that paper, Rp-cAMP, a cAMP antagonist, suppressed VEGF expression induced by PGE2 (23). cAMPdependent increase in VEGF expression was also observed in isolated organs such as perfused rat lungs and human fetal lung explants (24,25).…”
Section: Discussionmentioning
confidence: 82%
“…In the lung, alveolar type II cells are the major source of VEGF (1,19,25,33), the epithelial cells that secrete surfactant and maintain alveolar epithelial renewal (11). VEGF production by type II cells is upregulated by hypoxia (27).…”
mentioning
confidence: 99%
“…It has also been shown that oxidative stress inactivates the survival signal of VEGF in endothelial cells through the action of peroxynitrite (Acarregui et al, 1999) .…”
Section: Effects Of Oxidative Stress On Pulmonary Vegf Expression Andmentioning
confidence: 99%
“…In an in vitro study of human foetal lungs, Acarregui et al (Acarregui et al, 1999) found increased levels of VEGF mRNA when the lung tissue was maintained in dexamethasone for 4 days as from the onset of incubation in 0.20 FiO 2 . However, when the epithelium was first incubated in FiO 2 0.20 and then treated with dexamethasone, mRNA levels were not increased.…”
Section: Effects Of Betamethasone Vs Dexamethasone On the Expression mentioning
confidence: 99%
See 1 more Smart Citation